4-6x-5x=-106

Simple and best practice solution for 4-6x-5x=-106 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-6x-5x=-106 equation:


Simplifying
4 + -6x + -5x = -106

Combine like terms: -6x + -5x = -11x
4 + -11x = -106

Solving
4 + -11x = -106

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + -11x = -106 + -4

Combine like terms: 4 + -4 = 0
0 + -11x = -106 + -4
-11x = -106 + -4

Combine like terms: -106 + -4 = -110
-11x = -110

Divide each side by '-11'.
x = 10

Simplifying
x = 10

See similar equations:

| (1/2)x^2-34=0 | | 12overy=3 | | 9b=100-46 | | (1/2)x*x | | 4-g/5=-3 | | 60+75+x+2=180 | | 70-t=31 | | (1/2)x(x) | | 1.3=5.7-y | | 18-3+(-5)=x | | 8x=12/1-2/3 | | -8+4x=-16x+26x | | 6x^2+14=2x | | 2x^2+7x=32 | | 7x=15/1-2/3 | | 6=r-27 | | 22-a=15 | | 4x=10/1-1/3 | | 3/2logx=1000 | | 07x+5(2x-3)=6 | | 5x=20/1-3/4 | | x^(3/2)=1000 | | 7-(-7+3x)=25x | | (5+w)(5w+4)=0 | | x^3/2=1000 | | x/5-(-15)=65 | | 4(x+2)-(x+5)-1= | | 28n^2=98-18n | | 4=v+1.2 | | 7.5=u-1.3 | | 4(x^2+3)=24 | | -(-10+2x)=2x+4 |

Equations solver categories